Diagnostic Performance of Diffusion-Weighted Magnetic Resonance Imaging in Patients with Cholesteatoma - Kayalı Dinç, A. Secil; Damgacı, Lale; Çayönü, Melih; Sözmen Cılız, Deniz; Boynueğri, Süleyman; Melih Şahin, M.; Gül Hatipoğlu, H.; Dogan, Naciye; Eryilmaz, Adil (ENT Updates, 2018)
Objective: Our aim was to evaluate the diagnostic performance of Magnetic Resonance Imaging (MRI) with diffusion-weighted images in patients with cholesteatoma. Methods: We compared the preoperative MRI findings and intraoperative microscopic examination findings in 54 patients who were operated on due to a pre-diagnosis of chronic otitis media with cholesteatoma, according to preoperative microscopic ear examination, temporal bone computed tomography (CT) and ear MRI. Results: Fifty-four patients (18 female and 36 male) were enrolled in this study. The mean age was 36.8 ± 17.3 (range: 6-67). Thirty-one patients had primary surgery, whereas 23 patients had revision surgery to the affected ear (for 19 patients, the second, for 3, the third, and for 1, the 5th operation).We found that the sensitivity of pre-operative MRI for detecting cholesteatoma was 97.7%, the specificity was 77.8%, and the diagnostic accuracy rate was 94.4%. The rate of false negatives in MRI with diffusion-weighted images was found to be 4% in primary cases, whereas the false negativity rate with this technique was found to be 0% for revision cases. Conclusion: We concluded that ear MRI examination with diffusion-weighted images is a significant diagnostic tool, to be used alongside preoperative history and physical examination in deciding on whether to operate, especially in patients for whom revision surgery of the ear (due to recurrent, residual, iatrogenic cholesteatoma, or squamous epithelium) is planned.